Compliance of Healthcare Workers with Hand Hygiene Practices in Neonatal and Pediatric Intensive Care Units: Overt Observation. (25th November 2014) - Karaaslan, Ayşe; Kepenekli Kadayifci, Eda; Atıcı, Serkan; Sili, Uluhan; Soysal, Ahmet; Çulha, Gülcan; Pekru, Yasemin; Bakır, Mustafa
Abstract : Background. The objective of this study was to assess the compliance of hand hygiene (HH) of healthcare workers (HCWs) in the neonatal and pediatric intensive care unit in a tertiary university hospital in Istanbul. Methods. An observational study was conducted on the compliance of HH for the five World Health Organization (WHO) indications. HCWs were observed during routine patient care in day shift. The authors also measured the technique of HH through hand washing or hand hygiene with alcohol-based disinfectant. Results. A total of 704 HH opportunities were identified during the observation period. Overall compliance was 37.0% (261/704). Compliance differed by role: nurses (41.4%) and doctors (31.9%) [P = 0.02, OR: 1.504, CI 95%: 1.058–2.137]. HCWs were more likely to use soap and water (63.6%) compared to waterless-alcohol-based hand hygiene (36.3%) [P < 0.05 ]. Conclusion. Adherence to hand hygiene practice and use of alcohol-based disinfectant was found to be very low. Effective education programs that improve adherence to hand hygiene and use of disinfectants may be helpful to increase compliance.